Health System Strengthening: Adopting WHO Building Blocks- Comparison between India and Indonesia - Shikha Gill (Masters Program in Public Health, Sebelas Maret University, 2018)
Background: The objective of this review was to review and compare between Indian and Indonesian health systems. It attempted to understand the health system strengthening activities adopted by both the countries.Subjects and Method: This was a systematic review using qualitative method. The internet-based search strategy extended the traditional approach of using bibliographic databases, journals, citations to include grey literature, abstracts, websites, reports and documents from WHO, World Bank, Ministry of Health Indonesia, and Ministry of Health and Family Welfare India.Results: The concept of designating household meeting requisite health standards as a healthy home is something which can be successfully implemented in India as social recognition plays a vital part in encouraging people to move towards healthier lifestyles. India is in the process of upgrading 150,000 Sub Centres into health and wellness centers. Comprehensive health care will be provided in these centers, including for mother and child health and noninfectious diseases. Essential drugs and diagnostic services will be provided free of cost at these centers. Another notable feature from India is the concept of ASHA which is an acronym and stands for Accredited Social Health Activist. ASHAs are locally selected and trained women who performed the duties of health promoters and educators in communities. The ASHA is trained to work as an intermediary between the public health system and the community. Medical Insurance coverage for Primary Care and the concept of VVIP Rooms at differential pricing is something which can be tried in Indian context while, the latest Government funded medical insurance for Secondary and Tertiary care and Strategic purchase from Private sector is something Indonesia can emulate. For tackling the rural health care problems : schemes like National Rural Health Mission (NRHM) and mandatory service in rural areas by doctors if they want government job can be looked at by Indonesian Health care professionals. The concept of Posyandu (Maternity Hut) and the registered midwife clinics is a unique concept which can be tried in Indian Context.Conclusion: The Indian and Indonesian health care systems have been compared and contrasted.Keywords: health care system, India, IndonesiaCorrespondence: Shikha Gill. International Institute of Health Management Research, New Delhi, India.Email: shikhaparttapgill@gmail.comJournal of Health Policy and Management (2018), 3(2): 101-107https://doi.org/10.26911/thejhpm.2018.03.02.06